TINGKAT PENDAPATAN NELAYAN HAND LINE TUNA DI PELABUHAN PERIKANAN TELUK AWANG DESA MERTAK KECAMATAN PUJUT, KABUPATEN LOMBOK TENGAH - Cahayani, Mimi; Sayuti, Muhamad (Nusantara Hasana Berdikari, 2022)
Fisherman is one of the people's jobs around the coast. By becoming fishermen, people are able to have sufficient income and even more. There are various types of fishermen, one of which is hand line tuna fishermen. Therefore, the researcher wanted to examine